Factors associated with thrombosis in pediatric patients with systemic lupus erythematosus. (June 2016) - Driest, K D; Sturm, M S; O'Brien, S H; Spencer, C H; Stanek, J R; Ardoin, S P
Objective: The risk of thrombosis is increased in patients with systemic lupus erythematosus (SLE). Few studies have assessed factors associated with thrombosis within the pediatric SLE (pSLE) population. We sought to better characterize these associated factors in pSLE patients using the Childhood Arthritis & Rheumatology Research Alliance (CARRA) registry. Methods: Within the CARRA registry, patients with a history of thrombosis were compared to those without. Univariate logistic regression was used to calculate odds ratios. A multivariable logistic regression model was conducted that included variables from the univariate analysis that had a p value < 0.10 and other variables identified as clinically significant from published literature. Results: Among the 979 pSLE patients in the CARRA registry, 24 (2.5%) patients had a history of arterial thrombosis and 35 (3.6%) of venous thrombosis. In the univariate analysis, the odds ratio of having a thrombotic event were found to be significantly higher in patients with a history of vasculitis, avascular necrosis (AVN), or antiphospholipid antibody (aPL). Similar results were found for vasculitis, AVN, and aPL in the multivariable analysis. Conclusion: Our study of pSLE patients suggests that vasculitis, positive APL, and AVN are associated with thrombotic events in this population.